Refugee sponsorship: A descriptive systematic review - Rovetta Cortés, Ana Irene (2022)
In the last decade 17 Western countries have adopted “sponsorship schemes” as a response to the “refugee crisis”. The review and systematization of 43 publications on such initiatives allow us to identify important differences in their design and scope in each of the World regions in which they have been implemented (North America, Oceania, Europe and Latin America). Additionally, we observe that there are more authors in favour of this type of strategies that those who question it, regardless of it being a privatized route of resettlement, a family reunification mechanism, a humanitarian admission stream or, simply, an amateur support project. The analysis enables us to recognize 2 principles different from the principle of additionality that characterizes the original model of refugee sponsorship. This suggests that economistic and humanitarian readings are eclipsing political and human rights-centered interpretations.